A modified immune clone algorithm for energy-saving scheduling in permutation flow shop - Yang, Yang; Qi, Wang Yong (Journal of physics. Conference series, 2018)
For the permutation flow shop scheduling problem, an energy-saving scheduling model has been presented considering the energy consumption and idle time of deferment machines. The mathematical programming model was established to minimize the total energy consumption for idle time, and a modified immune clone algorithm was developed. Four mutation operators have been introduced to ensure its exploration ability. Meanwhile, a LCS-EDA neighbor search method was presented based on estimation of distribution algorithm, which aims to enhance the exploitation ability of MICA. Finally, the experiments were carried out based according to two standard testing collections. The results have validated the feasibility and effectiveness of the proposed energy-saving model and modified metaheuristic.